Inattention and distraction in fatal road crashes – Results from in-depth crash investigations in Norway. (April 2019) - Sundfør, Hanne Beate; Sagberg, Fridulv; Høye, Alena
Highlights: Reports from in-depth studies of fatal crashes in Norway 2011–2015 have been reviewed. Inattention among drivers contributes to 29% of all fatal crashes in Norway. Distraction by use of mobile phones contributes to 2–4 % of all fatal crashes. Collision with pedestrians is the most frequent type of inattention-related crashes. Failure to check for information is a typical form of inattention. Abstract: Distraction and inattention pose a considerable threat to road safety, not only for car drivers, but also for vulnerable road users. Previous studies show that inattention and distraction are more often contributing factors in severe crashes, compared to less severe crashes. The correlation with severity appears to vary with the type of inattention. The aim of the present study was to conduct a comprehensive mapping of the types of inattention that contribute to fatal road crashes. This was done by exploring data from in-depth investigations of all fatal road crashes in Norway between 2011 and 2015 conducted by crash investigation teams of the Norwegian Public Roads Administration. Crash reports were selected for screening, based on codes indicating inattention as a possible contributing factor. Inattention among at-fault drivers of motor vehicles was found to contribute to almost one out of three fatal road crashes between 2011 and 2015. About one-third of inattention-related crashes involved pedestrians who were hit by motor vehicles, where the driver typically detected the pedestrian too late. Failure to check for information in blind spots or behind other sight obstructions is a typical form of inattention. Distraction by use of mobile phones contributed to between two and four percent of all fatal crashes, while other sources of distraction, within or outside of the vehicle, contributed to about ten percent. Driver inattention may be preventable by a system-oriented approach including a combination of vehicle technology, road and road environment improvements, appropriate signs and markings, education and information, as well as legal measures and enforcement regarding use of mobile phones, in-vehicle sight obstructions, and involvement in other secondary tasks during driving.